Technical Nuances in the Perioperative Management of Chronic Subdural Hematoma by Twin Burr Hole Craniostomy: Tips, Tricks, and Tactics - Sethi, Jatin K.; Harsh, Viraat; Kumar, Prashant; Sahay, Chandra B.; Kumar, Anil (Indian Journal of Neurotrauma, 2024)
Chronic subdural hematoma (CSDH) remains to be the most common neurosurgical entity usually encountered in the elderly population. With an increasing life expectancy and associated comorbidities, the incidence of CSDH is ever increasing. There is a lack of uniformity among neurosurgeons regarding management of CSDH, but surgical evacuation using twin burr hole craniostomy remains to be the most preferred modality. Other options available are twist drill craniostomy and craniotomy. A conservative approach may be preferred in a thin subdural hematoma with no or minimal neurological deficit or in high operative risk patients. Complications such as pneumocephalus, recollection, or rebleeding may be seen following surgical evacuation of CSDH. Herein we aimed to address the technical nuances associated with twin burr hole evacuation of CSDH to reduce the complications and the overall associated morbidity and mortality.
Keywords: chronic subdural hematoma; craniostomy; burr hole evacuation